The body [compact disc, unabridged] : a guide for occupants - Bryson, Bill (Random House Audio, 2019)
"Bill Bryson... guides us through the human body--how it functions, its remarkable ability to heal itself, and (unfortunately) the ways it can fail. Full of extraordinary facts (your body made a million red blood cells since you started reading this) and irresistible Bryson-esque anecdotes, The Body will lead you to a deeper understanding of the miracle that is life in general and you in particular."--Container.